RETRACTED: Tregs depletion aggravates activation of astrocytes by modulating IL-10/GXP4 following cerebral infarction - Wang, Shuai; Shi, Yubin; Zhang, Yanqi; Yuan, Fengyun; Mao, Mintao; Ma, Jun (Frontiers in Immunology, 2023)
Background Tregs plays a critical role in the development of secondary injuries in diseases. Accumulating evidence suggests an association between ischemic stroke and renal dysfunction; however, the underlying mechanisms remain unclear. This study aimed to investigate the potential of Tregs in inhibiting the activation of astrocytes after focal cerebral infarction. Methods This study aimed to investigate the renal consequences of focal cerebral ischemia by subjecting a mouse model to transient middle cerebral artery occlusion (tMCAO). Subsequently, we assessed renal fibrosis, renal ferroptosis, Treg infiltration, astrocyte activation, as well as the expression levels of active GPX4, FSP1, IL-10, IL-6, and IL-2 after a 2-week period. Results In the tMCAO mouse model, depletion of tregs protected against activation of astrocyte and significantly decreased FSP1, IL-6, IL-2, and NLRP3 expression levels, while partially reversing the changes in Tregs. Mechanistically, tregs depletion attenuates renal fibrosis by modulating IL-10/GPX4 following cerebral infarction. Conclusion Tregs depletion attenuates renal fibrosis by modulating IL-10/GPX4 following cerebral infarction.